Peran Dinas Komunikasi dan Informatika Kabupaten Lamongan dalam Pengambilan Keputusan Melalui Program Megilan Inovasi dan Teknologi - Ela Mardianti (Universitas 17 Agustus 1945 Semarang, 2026)
The Lamongan Regency Communication and Informatics Office plays a strategic role in supporting regional government decision-making through the implementation of the Megilan Innovation and Technology Program. The role of the Lamongan Regency Communication and Informatics Office in this program is realized as the main manager of digital information and archive systems that serve as the basis for providing data and information for regional leaders. Through the Megilan Innovation and Technology Program, the Communication and Informatics Office is responsible for everything from formulating archive digitization policies, implementing technology-based incoming mail management techniques, to providing fast, accurate, and integrated information to support the decision-making process. This study uses a descriptive qualitative method with interview and observation techniques carried out in the context of internship activities at the Lamongan Regency Communication and Informatics Office. Data analysis was carried out using the Miles and Huberman model which includes data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that archive digitization through the Megilan Innovation and Technology Program can accelerate information access, improve the accuracy of letter disposition, and strengthen transparency and accountability of regional government. However, obstacles are still found in the form of limited human resources, technological infrastructure, and synchronization of physical and digital archives. Therefore, strengthening organizational capacity and supporting policies is necessary to ensure the Communication and Informatics Agency's role in decision-making can be optimal and sustainable